Improving energy conversion efficiency for triboelectric nanogenerator with capacitor structure by maximizing surface charge density. Issue 5 (19th December 2014) - He, Xianming; Guo, Hengyu; Yue, Xule; Gao, Jun; Xi, Yi; Hu, Chenguo
Abstract : The charge density on a dielectric polymer is determined by capacitance and can be maximized by mixing the polymer with some carbon nanoparticles. Abstract : Nanogenerators with capacitor structures based on piezoelectricity, pyroelectricity, triboelectricity and electrostatic induction have been extensively investigated. Although the electron flow on electrodes is well understood, the maximum efficiency-dependent structure design is not clearly known. In this paper, a clear understanding of triboelectric generators with capacitor structures is presented by the investigation of polydimethylsiloxane-based composite film nanogenerators, indicating that the generator, in fact, acts as both an energy storage and output device. Maximum energy storage and output depend on the maximum charge density on the dielectric polymer surface, which is determined by the capacitance of the device. The effective thickness of polydimethylsiloxane can be greatly reduced by mixing a suitable amount of conductive nanoparticles into the polymer, through which the charge density on the polymer surface can be greatly increased. This finding can be applied to all the triboelectric nanogenerators with capacitor structures, and it provides an important guide to the structural design for nanogenerators. It is demonstrated that graphite particles with sizes of 20–40 nm and 3.0% mass mixed into the polydimethylsiloxane can reduce 34.68% of the effective thickness of the dielectric film and increase the surface charges by 111.27% on the dielectric film. The output power density of the triboelectric nanogenerator with the composite polydimethylsiloxane film is 3.7 W m −2, which is 2.6 times as much as that of the pure polydimethylsiloxane film.